PENGARUH MODEL PEMBELAJARAN QUANTUM DENGAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN NGRUKEM KECAMATAN MLARAK KABUPATEN PONOROGO - Nindya Arianulva Saksitasari; Hagus Muryanto; Raras Setyo Retno (Florea : Jurnal Biologi dan Pembelajarannya, 2016)
This research aims to determine whether there is influence of quantum learning model with the audio visual media to science learning outcomes student class V SDN Ngrukem Mlarak District of  Ponorogo in academic year 2015/2016. Due to very low yields Science learning and teachers teaching with conventional methods. This study uses a one-group pretest-posttest design. The research sample of 15 students and research instruments in the form of a multiple choice test. Datawere analyzed by using t-test. The result showed there are significant quantum learning model with audio visual media to science learning outcomes student class V SDN Ngrukem Mlarak District of Ponorogo in academic year 2015/2016.